The constant c of Lagrange's theorem for \[f\left( x \right)=x\left( x-1 \right)\left( x-2 \right)\] in \[\left[ 0,\dfrac{1}{2} \right]\] is
\[\begin{align}
& A.\dfrac{1}{2} \\
& B.\dfrac{6+\sqrt{21}}{6} \\
& C.\dfrac{6-\sqrt{21}}{6} \\
& D.\dfrac{\sqrt{21}-6}{6} \\
\end{align}\]
Answer
Verified
483.6k+ views
Hint: To solve the question given above, we will use the concept of Lagrange's mean value theorem (LMVT). So, first we will find out what is LMVT and then using it, we will find the value of \[f'\left( c \right)\] as shown below:
\[f'\left( c \right)=\dfrac{f\left( b \right)-f\left( a \right)}{b-a}\]
Then, we will find the derivative of the function \[\left( f'\left( x \right) \right)\] and put c in place of it. We will solve the quadratic in c with the help of the quadratic formula.
Complete step by step answer:
Before we solve the question, we must know what Lagrange’s mean value theorem (LMVT) is. Lagrange's mean value theorem (LMVT) states that if a function \[f\left( x \right)\] is continuous on closed interval \[\left[ a,b \right]\] and differentiable on the open interval \[\left( a,b \right)\] then there is at least one point \[x=c\] on this interval, such that:
\[f'\left( c \right)=\dfrac{f\left( b \right)-f\left( a \right)}{b-a}\]
In our case, \[f\left( x \right)=x\left( x-1 \right)\left( x-2 \right)\] which is continuous and differentiable in the interval \[\left[ 0,\dfrac{1}{2} \right]\] .Now, we will calculate \[f'\left( c \right)\] first with the help of LMVT. In our case, \[a=0\,\,\text{and }b=\dfrac{1}{2}\] Thus, we have:
\[\begin{align}
& f'\left( c \right)=\dfrac{f\left( \dfrac{1}{2} \right)-f\left( 0 \right)}{\dfrac{1}{2}-0} \\
& \Rightarrow f'\left( c \right)=\dfrac{f\left( \dfrac{1}{2} \right)-f\left( 0 \right)}{\left( \dfrac{1}{2} \right)} \\
& \Rightarrow f'\left( c \right)=2\left( f\left( \dfrac{1}{2} \right)-f\left( 0 \right) \right)......................(i) \\
\end{align}\]
Now, we will calculate the values of \[f\left( \dfrac{1}{2} \right)\text{ and }f\left( 0 \right)\] Thus, we have:
\[\begin{align}
& f\left( \dfrac{1}{2} \right)=\left( \dfrac{1}{2} \right)\left( \dfrac{1}{2}-1 \right)\left( \dfrac{1}{2}-2 \right) \\
& \Rightarrow f\left( \dfrac{1}{2} \right)=\dfrac{1}{2}\times \left( \dfrac{-1}{2} \right)\left( \dfrac{-3}{2} \right) \\
& \Rightarrow f\left( \dfrac{1}{2} \right)=\dfrac{3}{8}\,.........................(ii) \\
\end{align}\]
\[\begin{align}
& f\left( 0 \right)=0\left( 0-1 \right)\left( 0-2 \right) \\
& f\left( 0 \right)=0\left( -1 \right)\left( -2 \right) \\
& f\left( 0 \right)=0\,.......................(iii) \\
\end{align}\]
Now, we will put the values of \[f\left( \dfrac{1}{2} \right)\text{ and }f\left( 0 \right)\] from (ii) and (iii) to (i). Thus, we will get:
\[\begin{align}
& \Rightarrow f'\left( c \right)=2\left( \dfrac{3}{8}-0 \right) \\
& \Rightarrow f'\left( c \right)=2\left( \dfrac{3}{8} \right) \\
& \Rightarrow f'\left( c \right)=\dfrac{3}{4}\,........................(iv) \\
\end{align}\]
Now, we will find \[f'\left( x \right)\] i.e. the derivative of f(x). For doing this, we will expand f(x) first. Thus, we will get:
\[\begin{align}
& f\left( x \right)=x\left( x-1 \right)\left( x-2 \right) \\
& \Rightarrow f\left( x \right)=x\left( {{x}^{2}}-x-2x+2 \right) \\
& \Rightarrow f\left( x \right)=x\left( {{x}^{2}}-3x+2 \right) \\
& \Rightarrow f\left( x \right)={{x}^{3}}-3{{x}^{2}}+2x \\
\end{align}\]
Now \[f'\left( x \right)\] will be:
\[\begin{align}
& f'\left( x \right)=\dfrac{d}{dx}\left[ f\left( x \right) \right]=\dfrac{d}{dx}\left[ {{x}^{3}}-3{{x}^{2}}+2x \right] \\
& f'\left( x \right)=3{{x}^{2}}-6x+2 \\
\end{align}\]
Thus, the value of \[f'\left( x \right)\] will be:
\[f'\left( c \right)=3{{c}^{2}}-6c+2\,.......................(v)\]
From (iv) and (v), we have:
\[\begin{align}
& \Rightarrow 3{{c}^{2}}-6c+2\,=\dfrac{3}{4} \\
& \Rightarrow 3{{c}^{2}}-6c+2-\dfrac{3}{4}\,=0 \\
& \Rightarrow 3{{c}^{2}}-6c+\dfrac{5}{4}\,=0 \\
& \Rightarrow 12{{c}^{2}}-24c+5\,=0 \\
\end{align}\]
Now, the above equation is a quadratic in c. So, we will find the value of c using the quadratic formula. If the quadratic equation given is \[a{{x}^{2}}+bx+c=0\] then we have:
\[x=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}\]
Thus, we have:
\[\begin{align}
& c=\dfrac{-\left( -24 \right)\pm \sqrt{{{\left( -24 \right)}^{2}}-4\left( 12 \right)\left( 5 \right)}}{2\left( 12 \right)} \\
& \Rightarrow c=\dfrac{24\pm \sqrt{576-240}}{24} \\
& \Rightarrow c=\dfrac{24\pm \sqrt{336}}{24} \\
& \Rightarrow c=\dfrac{24\pm 4\sqrt{21}}{24} \\
& \Rightarrow c=\dfrac{6\pm \sqrt{21}}{6} \\
\end{align}\]
Now, either \[c=\dfrac{6+\sqrt{21}}{6}\] or \[c=\dfrac{6-\sqrt{21}}{6}\] or both:
If \[c=\dfrac{6+\sqrt{21}}{6}\] then \[c=\dfrac{6+4.58}{6}\]
\[\begin{align}
& \Rightarrow c=\dfrac{10.58}{6} \\
& \Rightarrow c=1.76 \\
\end{align}\]
If \[c=\dfrac{6-\sqrt{21}}{6}\] then \[c=\dfrac{6-4.58}{6}\]
\[\begin{align}
& \Rightarrow c=\dfrac{1.42}{6} \\
& \Rightarrow c=0.23 \\
\end{align}\]
So, the value of \[c=\dfrac{6-\sqrt{21}}{6}\] because the interval of c is \[\left[ 0,\dfrac{1}{2} \right]\]
So, the correct answer is “Option C”.
Note: We have not checked whether \[f\left( x \right)=x\left( x-1 \right)\left( x-2 \right)\] is continuous or differentiable in \[\left[ 0,\dfrac{1}{2} \right]\] This is because f(x) is a cubic polynomial and every cubic polynomial is continuous and differentiable in the \[x\in \left( -\alpha ,\alpha \right)\] If we want, we can check this by applying the limit on f(x).
\[f'\left( c \right)=\dfrac{f\left( b \right)-f\left( a \right)}{b-a}\]
Then, we will find the derivative of the function \[\left( f'\left( x \right) \right)\] and put c in place of it. We will solve the quadratic in c with the help of the quadratic formula.
Complete step by step answer:
Before we solve the question, we must know what Lagrange’s mean value theorem (LMVT) is. Lagrange's mean value theorem (LMVT) states that if a function \[f\left( x \right)\] is continuous on closed interval \[\left[ a,b \right]\] and differentiable on the open interval \[\left( a,b \right)\] then there is at least one point \[x=c\] on this interval, such that:
\[f'\left( c \right)=\dfrac{f\left( b \right)-f\left( a \right)}{b-a}\]
In our case, \[f\left( x \right)=x\left( x-1 \right)\left( x-2 \right)\] which is continuous and differentiable in the interval \[\left[ 0,\dfrac{1}{2} \right]\] .Now, we will calculate \[f'\left( c \right)\] first with the help of LMVT. In our case, \[a=0\,\,\text{and }b=\dfrac{1}{2}\] Thus, we have:
\[\begin{align}
& f'\left( c \right)=\dfrac{f\left( \dfrac{1}{2} \right)-f\left( 0 \right)}{\dfrac{1}{2}-0} \\
& \Rightarrow f'\left( c \right)=\dfrac{f\left( \dfrac{1}{2} \right)-f\left( 0 \right)}{\left( \dfrac{1}{2} \right)} \\
& \Rightarrow f'\left( c \right)=2\left( f\left( \dfrac{1}{2} \right)-f\left( 0 \right) \right)......................(i) \\
\end{align}\]
Now, we will calculate the values of \[f\left( \dfrac{1}{2} \right)\text{ and }f\left( 0 \right)\] Thus, we have:
\[\begin{align}
& f\left( \dfrac{1}{2} \right)=\left( \dfrac{1}{2} \right)\left( \dfrac{1}{2}-1 \right)\left( \dfrac{1}{2}-2 \right) \\
& \Rightarrow f\left( \dfrac{1}{2} \right)=\dfrac{1}{2}\times \left( \dfrac{-1}{2} \right)\left( \dfrac{-3}{2} \right) \\
& \Rightarrow f\left( \dfrac{1}{2} \right)=\dfrac{3}{8}\,.........................(ii) \\
\end{align}\]
\[\begin{align}
& f\left( 0 \right)=0\left( 0-1 \right)\left( 0-2 \right) \\
& f\left( 0 \right)=0\left( -1 \right)\left( -2 \right) \\
& f\left( 0 \right)=0\,.......................(iii) \\
\end{align}\]
Now, we will put the values of \[f\left( \dfrac{1}{2} \right)\text{ and }f\left( 0 \right)\] from (ii) and (iii) to (i). Thus, we will get:
\[\begin{align}
& \Rightarrow f'\left( c \right)=2\left( \dfrac{3}{8}-0 \right) \\
& \Rightarrow f'\left( c \right)=2\left( \dfrac{3}{8} \right) \\
& \Rightarrow f'\left( c \right)=\dfrac{3}{4}\,........................(iv) \\
\end{align}\]
Now, we will find \[f'\left( x \right)\] i.e. the derivative of f(x). For doing this, we will expand f(x) first. Thus, we will get:
\[\begin{align}
& f\left( x \right)=x\left( x-1 \right)\left( x-2 \right) \\
& \Rightarrow f\left( x \right)=x\left( {{x}^{2}}-x-2x+2 \right) \\
& \Rightarrow f\left( x \right)=x\left( {{x}^{2}}-3x+2 \right) \\
& \Rightarrow f\left( x \right)={{x}^{3}}-3{{x}^{2}}+2x \\
\end{align}\]
Now \[f'\left( x \right)\] will be:
\[\begin{align}
& f'\left( x \right)=\dfrac{d}{dx}\left[ f\left( x \right) \right]=\dfrac{d}{dx}\left[ {{x}^{3}}-3{{x}^{2}}+2x \right] \\
& f'\left( x \right)=3{{x}^{2}}-6x+2 \\
\end{align}\]
Thus, the value of \[f'\left( x \right)\] will be:
\[f'\left( c \right)=3{{c}^{2}}-6c+2\,.......................(v)\]
From (iv) and (v), we have:
\[\begin{align}
& \Rightarrow 3{{c}^{2}}-6c+2\,=\dfrac{3}{4} \\
& \Rightarrow 3{{c}^{2}}-6c+2-\dfrac{3}{4}\,=0 \\
& \Rightarrow 3{{c}^{2}}-6c+\dfrac{5}{4}\,=0 \\
& \Rightarrow 12{{c}^{2}}-24c+5\,=0 \\
\end{align}\]
Now, the above equation is a quadratic in c. So, we will find the value of c using the quadratic formula. If the quadratic equation given is \[a{{x}^{2}}+bx+c=0\] then we have:
\[x=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}\]
Thus, we have:
\[\begin{align}
& c=\dfrac{-\left( -24 \right)\pm \sqrt{{{\left( -24 \right)}^{2}}-4\left( 12 \right)\left( 5 \right)}}{2\left( 12 \right)} \\
& \Rightarrow c=\dfrac{24\pm \sqrt{576-240}}{24} \\
& \Rightarrow c=\dfrac{24\pm \sqrt{336}}{24} \\
& \Rightarrow c=\dfrac{24\pm 4\sqrt{21}}{24} \\
& \Rightarrow c=\dfrac{6\pm \sqrt{21}}{6} \\
\end{align}\]
Now, either \[c=\dfrac{6+\sqrt{21}}{6}\] or \[c=\dfrac{6-\sqrt{21}}{6}\] or both:
If \[c=\dfrac{6+\sqrt{21}}{6}\] then \[c=\dfrac{6+4.58}{6}\]
\[\begin{align}
& \Rightarrow c=\dfrac{10.58}{6} \\
& \Rightarrow c=1.76 \\
\end{align}\]
If \[c=\dfrac{6-\sqrt{21}}{6}\] then \[c=\dfrac{6-4.58}{6}\]
\[\begin{align}
& \Rightarrow c=\dfrac{1.42}{6} \\
& \Rightarrow c=0.23 \\
\end{align}\]
So, the value of \[c=\dfrac{6-\sqrt{21}}{6}\] because the interval of c is \[\left[ 0,\dfrac{1}{2} \right]\]
So, the correct answer is “Option C”.
Note: We have not checked whether \[f\left( x \right)=x\left( x-1 \right)\left( x-2 \right)\] is continuous or differentiable in \[\left[ 0,\dfrac{1}{2} \right]\] This is because f(x) is a cubic polynomial and every cubic polynomial is continuous and differentiable in the \[x\in \left( -\alpha ,\alpha \right)\] If we want, we can check this by applying the limit on f(x).
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE